New Advanced Trigonometric Modeling of COVID-19 Cases in Saudi Arabia - Hazar A. Khogeer; Amani Alrumayh (Journal of Mathematics)
Conclusions: The new trigonometric Weibull distribution effectively modeled daily COVID-19 cases across various regions in Saudi Arabia, demonstrating superior fit and capturing complex epidemic dynamics. This study highlights the new trigonometric Weibull distribution distribution’s capability to detect significant trends and periodic fluctuations, enhancing public health response strategies. Its successful application underscores the value of advanced trigonometric models in epidemiological research and pandemic management.